Renovating with vacuum insulation panels - Testing of alternative core material and a renovation case study - Bergström, Sara (My University, 2020)
The building sector needs to save energy and the regulations are becoming stricter with regards to energy used for heating. The regulations also apply to renovations, and for some buildings with cultural value external insulation is not a possibility. To minimise the loss of real estate with internal insulation, super insulation materials might be used. For one such material, vacuum insulation panels (VIP), the production process is energy consuming. Previous research has shown that the core materials contribute to around 90% of the total production energy of the panels, and a decrease of up to 45% would be possible with alternative core materials and procedures. In this study, a possible alternative core material made from algae was tested and characterized with regard to specific heat capacity, density, hygroscopic properties and thermal conductivity. Based on calculations of the thermal conductivity at different pressure, the performance as a core material in a VIP was estimated. The tests and calculations show that the material made from algae does not have the properties that would make it suitable to be a core material in VIP at the current conditions, but further development and more research is needed. On the building scale, thermal bridges are another aspect of saving energy which become more dominant when insulating with a super insulation material. Simulations to estimate the thermal bridges in a brick building from 1890 with internal insulation of VIP were performed. The study focused on the thermal bridges at and around the floor joist. The results of the simulations show that the thermal bridge from the floor joist is responsible for almost 50% of the total heat flow through the insulated wall. The thermal bridges around the VIP is small in comparison and may, in this scenario, be neglected. However, it may be of more importance in other buildings.
Keywords: Super insulation materials, vacuum insulation panel, VIP, thermal bridge, core material